Challenges and Risks in Ecotourism Management: Issues and Opportunities - Amaechi Nwankwo, Elochukwu; Emilia Kayode, Chinonye (Eco-Tourism and Sustainable Development, 2025)
Ecotourism has been identified as among the bedrocks of tourism development in some parts of Africa. These include nations in eastern Africa, southern Africa and part of western Africa. These countries have over the years, leveraged on the opportunities of ecotourism to compete favourably in the global tourism market. However, various issues and challenges have undermined these huge opportunities of ecotourism for tourism development in a place. This study is aimed at examining some of these challenges and recommending various measures that can be applied to promote sustainable ecotourism development in Nigeria and other parts of Africa. The study used field observation and key informant interview approaches in qualitative research. It also adopted a literature method to understand the literary contributions to the subject matter. Identified challenges were classified under environmental, social and economic challenges. The study also considered risks associated with mass tourism in ecotourist destinations. At the end various measures were recommended to facilitate sustainable ecotourism management in Nigeria and other parts of Africa. The study has implications for sustainable ecotourism management in Africa, especially those places with huge ecotourism opportunities, but with less capacity for sustainable management. This is imperative hence ecotourism derives a fair share of the economic fortunes of those nations.